Immatures of Lamprosoma amethystinum Perty, 1832 (Chrysomelidae, Lamprosomatinae) - Casari, Sônia A.; Teixeira, Édson Possidônio (Zootaxa, 2008)
The larva and pupa of Lamprosoma amethystinum Perty, 1832, collected on Terminalia catappa L., are described and illustrated. Biological notes and a comparison among the immatures of Lamprosoma are included. A comparison between the larvae of L. amethystinum Perty and Oomorphus concolor (Sturm) is also presented.